Profil daerah kabupaten dan kota - Penerbit Buku Kompas (Jakarta : Penerbit Buku Kompas, 2001)
Socio-economic conditions of kabupaten and cities in Indonesia
Includes index
Keywords: Local government -- Indonesia; Indonesia -- Politics and government -- 1998-; Indonesia -- Economic conditions -- 1997-; Indonesia -- Social conditions